Guidelines for Foreign Exchange Reserve Management : Accompanying Document and Case Studies. (Manuals and Guides, 2005)
This accompanying document to the Guidelines for Foreign Exchange Reserve Management, which the IMF published in 2004, presents case studies prepared by reserve management entities in 20 countries. These sample case studies illustrate how a range of countries from around the world, at different stages of economic and financial development and institutional structure, have developed their capacity in reserve management in the areas covered by the Guidelines. The various strategies adopted by the countries, which are based on the country-specific policy environment, offer useful insights and suggestions to countries seeking to strengthen their policy frameworks for reserve management.